The Degree of Knee Extension Does Not Affect Postoperative Stability or Subsequent Graft Tear Rate After Anterior Cruciate Ligament Reconstruction With Patellar Tendon Autograft. (April 2016) - Benner, Rodney W.; Shelbourne, K. Donald; Gray, Tinker
Background: There is concern that high degrees of hyperextension may lead to an increase in graft laxity or graft failure after anterior cruciate ligament (ACL) reconstruction. Hypothesis: Patients with a high degree of hyperextension will have a higher rate of graft tear/failure and lower subjective scores after surgery compared with patients with less knee extension. Study Design: Cohort study, Level of evidence, 2. Methods: Of 2329 patients who underwent ACL reconstruction with patellar tendon autograft between 1998 and 2008, there were 625 patients who met the inclusion criteria of having primary ACL surgery, no bilateral ACL injuries, no existing osteoarthritis, and having either ≥6° of knee hyperextension before and after surgery (group A: n = 318; mean hyperextension, 8° ± 2° [range, 6°-15°]) or ≤3° of knee hyperextension before and after surgery (group B: n = 307; mean hyperextension, 0° ± 3° [range, 3° hyperextension to −4° short of 0° neutral]). KT-1000 arthrometer manual maximum difference between knees, range of motion measurements, and subjective follow-up with International Knee Documentation Committee (IKDC) and Cincinnati Knee Ratings Scale (CKRS) surveys were used to evaluate results. Subsequent graft tear related to specific injury within 5 years of surgery was recorded. Graft failure was defined as a KT-1000 manual maximum difference of >5 mm. Results: Follow-up was obtained from 278 (87%) in group A and 275 (90%) in group B at a mean of 4.1 ± 1.1 years after surgery. The KT-1000 arthrometer manual maximum difference between knees was 2.0 ± 1.4 in group A and 2.1 ± 1.6 in group B ( P = .701). Subsequent ACL graft tear/failure occurred in 22 patients (6.9%) in group A and 30 patients (9.8%) in group B ( P = .246). Further subanalysis showed that the graft tear/failure rate was 6 of 81 (7.4%) for patients with ≥10° of hyperextension versus 16 of 237 (6.8%) for patients with 6° to 9° of hyperextension. There was no difference in IKDC or CKRS scores between groups after surgery ( P = .933 and .155, respectively). Conclusion: Obtaining full hyperextension that is anatomically normal for most patients does not affect objective stability, ACL graft tear/failure rates, or subjective scores after ACL reconstruction with patellar tendon autograft.